The effects of training volume on the performance of young elite weightlifters - Siahkouhian, M.; Kordi, H. (Journal of Human Kinetics, 2010)
The purpose of this study was to determine the effects of increasing training volume on improvements in performance, physical fitness test records, and body composition variables in young elite weight lifters. Sixteen young elite weightlifters who volunteered to participate in the study undertook the training program included specific weightlifting training with an 80%-90% of individual records. Volume of training increased according to the Fry et al. protocol. Training for subjects consisted primarily of large muscle mass exercises made up of front and back squats, overhead lifts, dead lifts, the snatch, clean and jerk, and their variations. Vertical jump height and rearward weight throws were determined using a force platform with specifically designed software and distance covered by the subjects to the nearest 1cm, respectively. No significant changes in snatch and clean & jerk records were observed from pre- to mid- and from mid- to post-testing phases (snatch: 75.18-34.58 vs. 71.61-22.07 vs. 74.46-33.74 kg, P.0.05; clean & jerk: 91.96-47.84 vs. 88.21-42.85 vs. 92.82-43.56 kg, P.0.05). There were no significant changes in the front squat records from pre-to mid and from mid-to post testing (111.57-48.57 vs. 109.07-49.80 vs. 108.79-49.46 kg; P.0.05). Results showed decreases (no significant) from pre]to mid testing but remarkable increase from mid- to post testing for back squat (130.36-56.79 vs. 125.89-57.48 vs. 163.07-101.90 kg; P.0.05). The data showed that performing additional session per day of high intensity weightlifting training does not lead to significantly greater improvements in performance of young elite weightlifters. Therefore, coaches could use one instead of two sessions of high intensity lifting training per day.